Occult Kidney Dysfunction in Children With Transfusion-Dependent Thalassemia - Nurwahida, Mohd Zikre; Nor A., Muhamad; Caroline S. Y., Eng; Nur E., Zailanalhuddin; Charles, Lai Dekun; Jen C., Foo; Suet L., Yap; Hany, Ariffin; Karmila, Abu Bakar (Frontiers in Pediatrics, 2021)
Background: Thalassemia is the commonest hemoglobinopathy in Southeast Asia. Kidney dysfunction is an underreported sequelae in children with thalassemia. We conducted a retrospective study to identify the prevalence of and predisposing factors for kidney dysfunction in children with transfusion-dependent thalassemia (TDT).